Elevated IFNA1 and suppressed IL12p40 associated with persistent hyperinflammation in COVID-19 pneumonia - Jeon, Kyeongseok; Kim, Yuri; Kang, Shin Kwang; Park, Uni; Kim, Jayoun; Park, Nanhee; Koh, Jaemoon; Shim, Man-Shik; Kim, Minsoo; Rhee, Youn Ju; Jeong, Hyeongseok; Lee, Siyoung; et al. (Frontiers in Immunology, 2023)
Despite of massive endeavors to characterize inflammation in COVID-19 patients, the core network of inflammatory mediators responsible for severe pneumonia still remain remains elusive. Here, we performed quantitative and kinetic analysis of 191 inflammatory factors in 955 plasma samples from 80 normal controls (sample n = 80) and 347 confirmed COVID-19 pneumonia patients (sample n = 875), including 8 deceased patients. Differential expression analysis showed that 76% of plasma proteins (145 factors) were upregulated in severe COVID-19 patients compared with moderate patients, confirming overt inflammatory responses in severe COVID-19 pneumonia patients. Global correlation analysis of the plasma factors revealed two core inflammatory modules, core I and II, comprising mainly myeloid cell and lymphoid cell compartments, respectively, with enhanced impact in a severity-dependent manner. We observed elevated IFNA1 and suppressed IL12p40, presenting a robust inverse correlation in severe patients, which was strongly associated with persistent hyperinflammation in 8.3% of moderate pneumonia patients and 59.4% of severe patients. Aberrant persistence of pulmonary and systemic inflammation might be associated with long COVID-19 sequelae. Our comprehensive analysis of inflammatory mediators in plasma revealed the complexity of pneumonic inflammation in COVID-19 patients and defined critical modules responsible for severe pneumonic progression.